6-Methylsalicylic Acid Production in Solid Cultures of Penicillium patulum Occurs Only When an Aerial Mycelium Is Present - Peace, J. N. (1981)
When Penicillium patulum was grown on Czapek-Dox agar, 6-methylsalicylic acid was produced as an aerial mycelium was forming. Nutrients were often plentiful in the medium when biosynthesis began. If the formation of an aerial mycelium was prevented by growing the fungus between two sheets of dialysis membrane, no 6-methylsalicylic acid was produced even when nutrients were completely consumed. If the upper sheet of dialysis membrane was stripped off cultures of the latter type, an aerial mycelium formed; concomitantly, 6-methylsalicylic acid biosynthesis was observed. We conclude that 6-methylsalicylic acid was produced only by P. patulum colonies that possessed an aerial mycelium.